Analysis of the Causes of Japanese-Korean Disputes from Constructivist Perspective - Phung, My Linh; Přikryl, Pavel; Rolenc, Jan Martin, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
Japan and the Republic of Korea are two developed democracies with many cultural similarities who are expected to cooperate closely on all levels to contribute to the region’s stability and prosperity. Nevertheless, the Japanese–South Korean relations are not only far from friendly, in the recent years they even deteriorated to the ‘historical low’. The illogical development of the relations featuring many fluctuations could not be explained by neither liberalism nor realism, as a result, the most plausible explanation is that the relations are not given but constructed. This construction is moreover significantly influenced by their national identities, the basis for national self-esteems. In all the major issues between South Korea and Japan, it is always national self-esteem, as interpreted by the political élites, which appears to obstruct any improvement and continues to shape the relations between Japan and South Korea today.
Vedoucí práce: Pavel Přikryl
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses